Privacy and Data Protection Concerns in the Regulatory Framework of Slovenian Energy Law - Dimović, Zoran (LeXonomica, 2023)
The implementation of smart energy systems (SES) in the Slovenian energy sector has raised significant privacy and data protection concerns. The collection and processing of personal data from energy consumers, as well as cybersecurity threats, pose risks that must be addressed. The legal framework governing privacy and data protection in the energy field in Slovenia is based on the GDPR, ZOEE, ZVPot-1, ZVOP-2 and others, which impose significant obligations on entities processing personal data. To mitigate these risks, exact terminology must be used to implement privacy, data protection and also cybersecurity measures and ensure compliance with the legal framework.PovzetekIzvajanje pametnih energetskih sistemov (SES) v slovenskem energetskem sektorju je sprožilo precejšnje pomisleke glede zasebnosti in varstva podatkov. Zbiranje in obdelava osebnih podatkov odjemalcev energije ter grožnje kibernetski varnosti predstavljajo tveganja, ki jih je treba obravnavati. Pravni okvir, ki ureja zasebnost in varstvo podatkov na področju energetike v Sloveniji, temelji na GDPR, ZOEE, ZVPot-1, ZVOP-2 itd., ki subjektom, ki obdelujejo osebne podatke, nalagajo pomembne obveznosti. Za zmanjšanje teh tveganj je treba uporabljati natančno terminologijo za izvajanje ukrepov na področju zasebnosti, varstva podatkov in tudi kibernetske varnosti ter zagotavljati skladnost s pravnim okvirom.
Keywords: cybersecurity; data protection; energy law; green and digital transformation; privacy protection